2009
DOI: 10.1074/jbc.m109.012096
|View full text |Cite
|
Sign up to set email alerts
|

Activation of an Olfactory Receptor Inhibits Proliferation of Prostate Cancer Cells

Abstract: Olfactory receptors (ORs) are expressed not only in the sensory neurons of the olfactory epithelium, where they detect volatile substances, but also in various other tissues where their potential functions are largely unknown. Here, we report the physiological characterization of human OR51E2, also named prostate-specific G-protein-coupled receptor (PSGR) due to its reported up-regulation in prostate cancer. We identified androstenone derivatives as ligands for the recombinant receptor. PSGR can also be activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
322
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 240 publications
(339 citation statements)
references
References 33 publications
13
322
2
2
Order By: Relevance
“…We were unable to detect a response to β-ionone for Olfr78 or OR51E2 in our luciferase-based reporter assay, and β-ionone also failed to elicit changes in BP when delivered intravenously. It is possible that this difference stems from the different methods used; Neuhaus et al (32) used a calcium imaging method to detect odorant responses, whereas we assayed cAMP (via luciferase). We did, however, confirm in a separate assay that activation of Olfr78 and OR51E2 by acetate or propionate produces a signal detectable by calcium imaging.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to detect a response to β-ionone for Olfr78 or OR51E2 in our luciferase-based reporter assay, and β-ionone also failed to elicit changes in BP when delivered intravenously. It is possible that this difference stems from the different methods used; Neuhaus et al (32) used a calcium imaging method to detect odorant responses, whereas we assayed cAMP (via luciferase). We did, however, confirm in a separate assay that activation of Olfr78 and OR51E2 by acetate or propionate produces a signal detectable by calcium imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Several kinds of olfactory receptors have been identified in tissues other than olfactory tissues, including the testis, tongue, and placenta; however, functions of most olfactory receptors expressed in nonolfactory tissues are still elusive (28). A previous study showed that an olfactory receptor, OR51E2, is expressed in prostate cancer cells and that activation of OR51E2 by its ligand, b-ionone and inhibited proliferation of prostate cancer cells (29). Another olfactory receptor family member, OR51E1, was reported to be a potential novel biomarker for small intestine neuroendocrine carcinoma (30).…”
Section: Discussionmentioning
confidence: 99%
“…As OR7C1 is expressed in primary spermatocytes, secondary spermatocytes, spermatid, and sperm in the testis, it may have a role in sperm chemotaxis. Inactivation of OR51E2 could reduce growth of prostate cancer cells via this pathway and then phosphorylation of p38 and stress-activated protein kinase/c-Jun NH 2 -terminal kinase (SAPK/JNK) MAPKs (29). The signaling pathway that induces the expression of stem cell-related genes via OR7C1 is still elusive, but activation of adenylate cyclase by Golf might be a possible pathway, and our preliminary data suggested that activation of Akt might also be involved in OR7C1 signal transduction (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Beginning in 2000, ORs have been repeatedly reported also to be expressed in non-olfactory tissues (De la Cruz et al 2009;Feldmesser et al 2006;Zhang et al 2007) where they play additional roles. Some ORs govern sperm chemotaxis (Fukuda and Touhara 2006;Spehr et al 2004), inhibit prostate cancer cell proliferation (Neuhaus et al 2009), regulate cell migration and adhesion in muscle (Griffin et al 2009), and regulate serotonin secretion of gastro-intestinal cells (Braun et al 2007;Kidd et al 2008). ORs are also reported to be tumor markers (Leja et al 2009;Weng et al 2005).…”
Section: Introductionmentioning
confidence: 99%